MENSURAÇÃO DE NÍVEIS DE ALFABETISMO NA BAHIA RURAL OITOCENTISTA: A REGIÃO OESTE | MEASUREMENT OF LITERACY RATES IN THE 18th CENTURY-RURAL-BAHIA: THE WESTERN REGION - Jesus, Adilson Silva de; Carneiro, Zenaide de Oliveira Novais; Lacerda, Mariana Fagundes de Oliveira (Estudos Linguísticos e Literários, 2017)
O contexto do Regulamento de 1854, da Lei 601, de 18 de setembro de 1850, conhecida como Lei de Terras, que propiciou o primeiro cadastramento fundiário do Brasil, estimulou a produção de variados documentos como, por exemplo, decretos, declarações, registros e editais. Os referidos documentos são usados, com frequência, em estudos acerca da questão fundiária no Brasil. Entretanto, em meio às novas perspectivas do fazer historiográfico, a História da Cultura Escrita, forma especifica da História Cultural, percebe esses manuscritos como registros materiais das práticas de escrita. Nessa perspectiva, o foco deste artigo é apresentar índices de alfabetismo, no interior da Bahia oitocentista, através da aplicação do método binário do cômputo das assinaturas, nas Declarações de Terras de Santana do Campo Largo, em períodos pré-censitário (1858-1859). Abstract: The context of the 1854 Regulation, from Law 601 of September 18th, 1850, known as the ‘Land Law’, which led to Brazil’s the first land registry, encouraged the production of a large number of documents, such as decrees, declarations, registries and edicts. These documents are frequently used in studies on land issues in Brazil. Notwithstanding, amid the new perspectives of historiographical work, the History of Written Culture, a specific form of Cultural History, sees these manuscripts as material records of writing practices. Following this perspective, the focus of this article is to present the literacy rates, in the countryside of 19th-century-Bahia, by applying the binary method of counting the subscriptions, in the ‘Land Act of Santana do Campo Largo’, prior to the census periods (1858-1859). Findings show an increased number of subscribers in the interior of rural Bahia of that century, pointing to a possible existence of a local elite, inserted in the written culture. Keywords: Literacy rates; Land Acts; Eighteenth-century-Bahia.